«In carne e ossa»: il corpo nelle opere di Georg Büchner - Roberta, Carnevale (Biblioteca di Studi di Filologia Moderna, 2009)
In the critical literature on Georg Büchner this monograph represents the first organic work devoted to the subject of the body - a pivotal issue for an understanding of his writings. The book investigates the significance assumed by the human body in three spheres of analysis: the political, the erotic and the scientific-philosophical. In the latter area the analysis hinges on the relations between Büchner's work and the writings of the three principal French materialist philosophers of the eighteenth century: La Mettrie, d'Holbach and Helvétius. The appraisal of this relation illustrates not only Büchner's appropriation of the legacy of ideas of French materialism, but also moments in which he satirises, sarcastically criticises or outrightly rejects certain central aspects of this vision of man and nature. From this analysis and the study of the political significance of the body and the erotic aspect, it emerges that the body, understood as Leib - human body, lived and living, the hub of subjective perception and experience - not only has a crucial function in the figurative layout of the literary works, but is also the focal point of Büchner's view of man, thus assuming a central importance both in the three areas examined and in the more strictly aesthetic sphere. This book won the Premio Associazione Sigismondo Malatesta "Opera Critica" - Letteratura, Teatro e Arti dello spettacolo - Edizione 2009.